Proceedings of SPE Improved Oil Recovery Symposium 2010
DOI: 10.2523/129978-ms
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost, High-Performance Chemicals for Enhanced Oil Recovery

Abstract: The ability to select low-cost, high-performance surfactants for a wide range of crude oils under a wide range of reservoir conditions has improved dramatically in recent years. We have developed surfactant formulations (surfactant, co-surfactant, co-solvent, alkali, polymer, electrolyte) using a refined phase behavior approach. Such formulations nearly always result in more than 90% oil recovery in both outcrop and reservoir cores when good surfactants with good mobility control are used. Chemical flood resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Yang et al (2010) recently reported numerous ASP core flooding results for viscous oils. Viscous oils with low API gravity are usually active (contain organic acids that react with alkali to form soap) so the use of alkali reduces the surfactant cost and makes ASP flooding economically attractive under many circumstances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al (2010) recently reported numerous ASP core flooding results for viscous oils. Viscous oils with low API gravity are usually active (contain organic acids that react with alkali to form soap) so the use of alkali reduces the surfactant cost and makes ASP flooding economically attractive under many circumstances.…”
Section: Resultsmentioning
confidence: 99%
“…When softening the injection water is not an option, chelating agents such as tetrasodium ethylene-diaminetetraacetate (EDTA-Na 4 ) can be used to sequester divalent cations, as reported by Yang et al (2010). However, EDTA-Na 4 is relatively expensive, and the required amount to complex divalent cations is higher than the theoretical value of 9 to 1 weight ratio as the temperature increases.…”
Section: Low-temperature and Low-salinity Active Oil In Carbonatementioning
confidence: 99%
“…. This effect can be understood using an activity diagram (Nelson et al, 1984;Zhao et al, 2008;Mohammadi et al, 2008;Yang et al, 2010). Furthermore, phase behavior experiments are used to determine the equilibration times and the quality of the microemulsion, such as microemulsion viscosities.…”
Section: Phase Behavior Experimentsmentioning
confidence: 99%
“…This is one of the most important requirements needed to achieve high oil recovery and low surfactant retention, and has been observed through core flood experiments (Dwarakanath et al, 2008, Yang et al, 2010. The surfactant solution in brine is often not clear near optimum salinity and may contain lamellar liquid crystals (Miller et al, 1986).…”
Section: Introductionmentioning
confidence: 95%